Phosphate functionalization of spongiolite surface - Melnikov, P.; Santagnelli, S. B.; dos Santos, F. J.; Delben, AAST; Delben, JRJ; Teixeira, ALR (Elsevier B.V., 2003)
Spongiolite from Mato Grosso do Sul (Brazil), natural inorganic composite constituted of silica needles, was treated with concentrated phosphoric acid at high temperatures. Superficial coating of the needles was proved to be constituted of silicon diphosphate, a compound offering six-coordinated silicon sites. Owing to the affinity of three charged ions to phosphate groups, this coating acts as specific adsorbent for the rare earth elements which prefer octahedral coordination (starting from samarium, yttrium included). The uptake of lanthanum and neodymium are significantly lower due to different coordination tendencies. Lanthanide fixation upon silica with PO4 groups anchored on its surface may be useful in the manufacturing of special phosphate-silicate glasses. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: spongolite; spongiolite; lanthanide sorption; phosphate group